2020
DOI: 10.1007/978-3-662-62138-7_55
|View full text |Cite
|
Sign up to set email alerts
|

Concept for Predicting Vibrations in Machine Tools Using Machine Learning

Abstract: Vibrations have a significant influence on quality and costs in metal cutting processes. Existing methods for predicting vibrations in machine tools enable an informed choice of process settings, however they rely on costly equipment and specialised staff. Therefore, this contribution proposes to reduce the modelling effort required by using machine learning based on data gathered during production. The approach relies on two sub-models, representing the machine structure and machining process respectively. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It can be shown that modal parameters are dependent on the axis positions of machine tools [13]. However, this is often not considered or not investigated in proposed methods [7,8,10,14,18].…”
Section: Review Of the State-of-the-art Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that modal parameters are dependent on the axis positions of machine tools [13]. However, this is often not considered or not investigated in proposed methods [7,8,10,14,18].…”
Section: Review Of the State-of-the-art Methodsmentioning
confidence: 99%
“…Approaches that use machine learning technologies show good results in modeling a system's dynamic behavior. However, they require extensive training data and are fixed to use cases they are trained for [18,19].…”
Section: Review Of the State-of-the-art Methodsmentioning
confidence: 99%
“…Recent advances in data‐driven approaches have demonstrated the advantages of resorting to comprehensive modeling, analysis, and prediction of dynamical systems solely based on available data 22 . Barton and Fleischer 23 presented the concept of predicting the vibrations in machine tools using machine learning (ML). Their idea was based on dividing the machining operation into two submodels, that is, process and machine models.…”
Section: Introductionmentioning
confidence: 99%